Anatomical Variant of Ulnar Nerve Trifurcation in Guyon’s Canal: Clinical Implications and Case Report - Savita Kanaujea, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Introduction: The ulnar nerve (UN), a continuation of the medial cord of the brachial plexus (C8, T1), traverses the medial aspect of the upper limb and enters the hand through Guyon's canal—a fibro-osseous tunnel located between the pisiform and the hook of the hamate bones. Within this canal, the UN typically bifurcates into a superficial sensory branch and a deep motor branch. However, anatomical variations, such as trifurcation, though rare, have been documented. Understanding these variations is crucial for clinicians, as they have significant implications in the diagnosis of entrapment neuropathies and during surgical interventions in the wrist and hand regions. Case Report: A cadaveric dissection was performed at the Department of Anatomy, King George’s Medical University, Lucknow following Cunningham’s Manual. A longitudinal incision was made along the medial forearm to the little finger. The ulnar nerve (UN) was exposed by retracting the flexor carpi ulnaris and traced through Guyon’s canal. An unusual trifurcation of the UN was observed in the right hand, while the left showed the typical bifurcation into superficial and deep branches. Division levels were noted with respect to the flexor retinaculum, medially between the pisiform and hook of hamate. Conclusion: Trifurcation of the ulnar nerve in the ulnar tunnel highlights the need for awareness of anatomical variations, which, though often asymptomatic, are clinically significant in entrapment neuropathies and surgery, aiding in diagnosis, prevention of injury, and surgical planning.